P18 Tumor free distance is the best predictive marker in patients with early-stage cervical cancer treated by primary surgery. (1st November 2019) - Cibula, D; Kocián, R; Dostálek, L; Fischerová, D; Germanová, A; Frühauf, F; Dundr, P; Němejcová, K; Jarkovský, J; Burgetová, A; Sláma, J
Abstract : Introduction/Background: Main limitation of the majority of previous studies on prognostic markers lied in an insufficient standardisation of both clinical management and the method of assessment of individual parameters. Methodology: All consecutive patients with early-stage cervical cancer treated by primary surgery in a single centre between 01/2007 and 12/2016 were eligible if they were assessed by standardized protocols for preoperative imaging and pathology. Fifteen prognostic parameters were evaluated, including age, 11 tumour-related (stage; largest tumour size; tumour size binarized; depth of stromal invasion; minimal tumour free distance (TFD); TFD binarized; lymphovascular space invasion (LVSI); tumour type; grade; parametrial invasion) and 3 lymph node (LN) status related ones (number of positive LNs; LN involvement; type of metastasis in LN). Results: Data from 378 consecutive patients were analysed. Table 1 shows characteristics of the whole group (Cohort A) and LN negative patients (Cohort B). All parameters were associated with a risk of recurrence (RR), except for age and grade, in Cohort A, but only 4 remained significant in Cohort B (tumor type, grade, minimal TFD, TFD binarized). The best predictive model for Cohort A entailed a combination of TFD≤3.5 mm and LN positivity, which discriminated a subgroup of 42 patients with RR 36% versus 6.5% in the rest of the cohort (figure1). In Cohort B a combination of TFD≤3.5 mm and adenosquamous tumour type discriminated a small group of 9 patients (RR 33% versus 6% (figure 2). Conclusion: TFD surpassed all other traditional tumor-related markers in the assessment of the recurrence risk in both cohorts. Predictive models combining TFD with LN status (whole cohort) or histological type (LN negative cases) can easily be used in daily practice and can identify the smallest possible group of patients with the highest risk of recurrence. Abstract P18 Table 1 Summary of demographic and clinical parameters in Cohort A (all cases) and Cohort B (LN neg) Disclosure: None of the authors declare a conflict of interest. Acknowledgements: This work was supported by Charles University in Prague (UNCE 204065 and PROGRES Q28/LF1), by the project of Ministry of Health of the Czech Republic (MZ CR - RVO VFN64165) and by a grant from the Czech Research Council (No 16-31643A).